ANALISIS HAMBATAN PENGKODEAN OLEH KODER TERHADAP SINGKATAN ISTILAH MEDIS DI RUMAH SAKIT UMUM DAERAH KOTA BAUBAU TAHUN 2020 - Wahyuni, Sri; Budiaty, Wa Ode Sitti (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
One of the main competencies of a medical recorder is coding diagnoses. Accuracy in coding a disease and action is very important because it is related to the financing of health services. In the implementation of JKN, the accuracy of the code given greatly influences the rates received by the hospital for the health services that have been provided. This study aims to provide an overview or description of the obstacles to officers' activities coding in coding related abbreviations of medical terms. The type of research used is descriptive research with qualitative methods, and a case study design. This research was carried out at the Baubau City Hospital, to be precise at the medical record unit at the Baubau City Hospital. The research was conducted in December 2020 - January 2021. The subjects or informants in this study were two officers coding in the medical record work unit of the Baubau Regional General Hospital. The object of this study is a medical record file containing abbreviations of medical terms. namely as many as 25 medical record files that only have medical term abbreviations in them.The research results show that there is Many abbreviations for medical terms are used in the Baubau City Hospital, but there is no guideline for the use of medical terms and abbreviations, and there is no Standard Operating Procedure that regulates the use of medical abbreviations. The obstacles in the activities of coding officers are related to abbreviations for medical terms, namely, the lack of officers coding, the writing of the diagnosis is unclear, the use of language is not uniform, the same abbreviation, and there is no abbreviation guide for medical terms.